Analisis Pendapatan Dan Kelayakan Usahatani Padi Sawah Di Subak Baturiti Desa Balinggi Kecamatan Balinggi Kabupaten Parigi Moutong - Supartama, I Made; Antara, Made; Rauf, Rustam Abd. (AGROTEKBIS, 2013)
This study aims to determine the level ofrice farming income and feasibility, and to know the development of Subak Baturiti in Balinggi Village, District of Balinggi, Parigi Moutong Regency. Respondent sampling is conducted purpossively. The number of respondent farmers taken in this study is 40 of 66 farmers living in Subak Baturiti. The analyzes used in this study are income analysis, feasibility analysis, and descriptive analysis. Results of those analyzes show the average rice production is 6.005,75 kg of harvested dried grains (HDG) and the average revenue received by the farmers is Rp 18.017.250,00 per farming unit (1,3 ha)/ growing season (GS) or Rp14.242.885,38/ha/GS, where as total costs spent by the respondent farmers are an average of Rp 12.692.780,18 per farming unit (1,3 ha)/GS, or Rp 10.033.818,32/ha/GS and th rice farmin revenue is Rp 5.324.469,83 per farming unit (1,3 ha) or Rp 4.209.067,06/ha/GS with R/C value = 1,42, showing that R/C value is higher than 1 (R/C > 1). Therefore the farming is favorable (additional benefit or revenue is higher than additional cost). Subak Baturiti is an organization of water user farmers, and implements the Tri Hita Karana Concept that there are interrelationships between human beings and God, between human beings and environment, and between human beings and their others so as the farming activities will go well dan harmoniously.